An economic history of bastardy in England and Wales - John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2006)
A remarkable feature of English demographic history is the explosion in childbearing outside marriage during the last quarter of the twentieth century, after 400 years of relative stability. Over the period 1845-1960, the percentage of births outside marriage moved within a small range, averaging about 5%. The paper finds that, up to the First World War, higher unemployment discouraged marriage and increased non-marital births, with a recovery in marriages in the subsequent year. This pattern is consistent with poorer labour market conditions discouraging marriages among pregnant would-be brides, thereby increasing bastardy. During the inter-war period, higher unemployment continued to produce postponement of marriages, but non-marital childbearing was no longer linked to unemployment, nor is there a clear link to unemployment in the post-war period. After 1960, when the contraceptive pill was introduced, childbearing outside marriage began to climb slowly, and it exploded after 1980, reaching 42% in 2004. This was partly driven by a steep increase in the age-specific non-marital births rates of women aged 20-34 from the mid-1970s to the early 1990s, after which they stabilised at a high level. At fixed average non-marital and marital agespecific birth rates, this increase in the proportion of births outside marriage can be mainly accounted for by a large fall in the proportion of women aged 20-34 who are married, which is in turn associated with a dramatic rise in cohabiting unions. These unions are short-lived before either dissolving or being converted into marriage. But this begs the question: why didnt average non-marital fertility rates fall when more women cohabited? Women had the means (contraception and legal abortion) to avoid nonmarital childbearing if they wanted to do so, and so the substitution of cohabiting unions for marriages need not have raised non-marital fertility. A theory of marriage market search (courtship) in which out-of-wedlock childbearing is an option suggests why it may be a rational choice, even when fertility can be controlled. A womans welfare as a single mother is likely to be influenced by the prevalence of single mothers in the population, which may reflect social stigma against single mothers. When their prevalence is low, nonmarital childbearing is discouraged. A temporary change in the determinants of non-marital childbearing that raises it, like the large rise in unemployment in the late 1970s/early 1980s, can produce rapid erosion of the stigma and a self-reinforcing rise in childbearing outside marriage. This dynamic is likely to be concentrated among a segment of the population who already had stronger incentives to have a child before marriage. If this social influence model is valid, then it is likely to be the case that socio-economic differences in the chances of having a child before marriage widen as childbearing outside marriage becomes more common, and the paper provides evidence that this has happened. An alternative, or complementary, explanation stresses the role of the rise in cohabiting unions and delay in partnership. These generated an increase in non-marital births by increasing the unmarried opulation. This view also points to the operation of a social influence model in explaining the dramatic rise in cohabitation, and the paper provides evidence of a diffusion of cohabiting unions from the better educated to the less educated population.
Keywords: 330